Manipulasi Nutrien dan Zat Pengatur Tumbuh untuk Meningkatkan Produksi dan Kualitas Buah Stroberi (Fragaria x ananassa) Kultivar BAT-1 - Gustania, Leolita; Tjahjoleksono, Aris; Ratnadewi, Diah (Jurnal Hortikultura Indonesia, 2023)
Indonesian farmers less frequently cultivate strawberry cv.BAT-1 because the fruit is less sweet, even though the cultivar is more adaptable to tropical conditions. Meanwhile, improving the quality and productivity of this cultivar is difficult for ordinary farmers. This study aimed to help increase the production and quality of strawberry BAT-1, i.e., the size, color, fruit sweetness, and shelf life, by manipulating some nutrients and hormones. This research was conducted in August - December 2021 and February - June 2022 (for the rainy and dry seasons, respectively) in Halimun-Salak, Bogor. This study used a factorial complete randomized design. The first stage of treatment was giving potassium and calcium and measuring vegetative parameters. Treatment with IBA and brassinolide was applied for the second stage, and generative parameters were measured. The results were that the treatments of potassium and calcium advanced and shortened the productive period. Combined with two growth regulators, they increased the fruit weight, anthocyanin content, and sweetness and decreased total acid value. D3I3B2 (PPC + CaCl2 2 g L on leaves and IBA 3 mM + BL 0.2 µM on fruits) was the best treatment in both seasons. Brassinolide (0.2 µM) extended the shelf-life of the fruit. Keywords: Brassinolide, brix, calcium, IBA, potassium